Optimalisasi BUMDES Berbasis OVOP (One Village One Product) Concept Di Kabupaten Pamekasan - Ardiansyah, Firman; Firdaus, Nabila Yuli; Muhtadi, Ridan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
This study aims to provide a conceptual model regarding the optimization of Village-Owned Enterprises (BUMDES) based on the OVOP (One Village One Product) concept as a flagship program, which is every BUMDES in Pamekasan Regency forms a community that leads to integrated community economic empowerment order to optimizing superior commodities in Pamekasan Regency each village. This study uses descriptive qualitative methods with secondary data collection methods obtained from literature and documentaries that have been processed. While the data analysis technique starts from editing, organizing and finding. The results showed that this program has the potential to be realized, seeing the superior commodities owned by each village in Pamekasan Regency are very many and varied, in addition to support from the government regarding the priority of using the 2021 Village Fund for BUMDES, this program is the right step in overcoming existing problems. This program can be an alternative that is able to create food self-sufficiency in Pamekasan Regency as well as become one of the exporters of domestic products spread to national and international regions.